2021
DOI: 10.30651/tell.v9i2.9482
|View full text |Cite
|
Sign up to set email alerts
|

Instagram Usage in Learning English: A Literature Review

Abstract: HighlightsSocial media of Instagram plays an important role in daily life communication and interaction also pledge a myriad potential learning to develop students' English skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…The other possibility for improvement of the experimental group in comparison to the control group in this study lies in the fact that diversity and novelty in the types of proposed tasks on Instagram immerse students in the learning activities (presentation and practice stages). This implication was supported by previous studies, which confirmed the influential role of Instagram as a MALL tool in boosting learners’ motivation, engagement, and attitudes toward learning ( Erarslan, 2019 ; Gonulal, 2019 ; Klimova and Polakova, 2020 ; Rasyiid et al, 2021 ; Guo, 2022 ). Taking a similar path, Chen Hsieh et al (2017) provide evidence for the effectiveness of LINE in sustaining an engaging and encouraging language learning atmosphere.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The other possibility for improvement of the experimental group in comparison to the control group in this study lies in the fact that diversity and novelty in the types of proposed tasks on Instagram immerse students in the learning activities (presentation and practice stages). This implication was supported by previous studies, which confirmed the influential role of Instagram as a MALL tool in boosting learners’ motivation, engagement, and attitudes toward learning ( Erarslan, 2019 ; Gonulal, 2019 ; Klimova and Polakova, 2020 ; Rasyiid et al, 2021 ; Guo, 2022 ). Taking a similar path, Chen Hsieh et al (2017) provide evidence for the effectiveness of LINE in sustaining an engaging and encouraging language learning atmosphere.…”
Section: Discussionsupporting
confidence: 80%
“…Social media platforms revolutionized language teaching and learning; they provided a socially engaging learning atmosphere ( Vadivel and Beena, 2019 ; Manca, 2020 ; Ahmadi and Tabatabaei, 2021 ; Rasyiid et al, 2021 ). More importantly, social media platforms are flexible; that is, they can be used across all educational settings (e.g., K-12 and higher education) as well as formal and informal learning contexts (e.g., Barrot, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, students' vocabulary can be expanded by following various Instagram accounts that focus on learning English, watching videos of them that provide English tutorials, and reading the captions below the videos. Rasyiid & Maulina (2021) agree that using Instagram can help with vocabulary development. They also suggest some strategies for increasing students' vocabulary.…”
Section: Perception Of Instagram Reels To Improve Speaking Skillmentioning
confidence: 91%
“…Teaching students using technology to learn, research, collaborate, and solve problems early will better prepare them for their careers. In addition, by learning to use technology at a young age, children develop the skills and knowledge crucial in today's world (Putra et al, 2021;Saputra et al, 2021;Rasyiid et al, 2021).…”
Section: Introductionmentioning
confidence: 99%